Discourse analysis of educational slogans: Shaping desires, aspirations, and social norms - Dabadi, Sunita (SADGAMAYA, 2024)
This study examines the transformative power of Language in educational marketing, with a particular focus on discourse in Nepalese secondary schools. Based on a critical discourse analysis, the research examines linguistic strategies for shaping the user’s desires, aspirations, and social norms. The study includes pragmatics, morphology and semantics, and discourse analysis. Four randomly selected schools in Kathmandu form the sample. The findings show that the slogans use language strategically to address institutional values and promote academic excellence, leadership development, and social and environmental responsibility. Linguistic analysis reveals the coherence of expressions, correspondence with discourse practices, implications, ideals, and preconceptions.